Genetic Variations and mRNA Expression of Goat DNAH1 and Their Associations with Litter Size - Zhen Wang; Ruolan Wang; Chuanying Pan; Hong Chen; Lei Qu; Lian Wu; Zhengang Guo; Haijing Zhu; Xianyong Lan (Cells, 2022)
Dynein Axonemal Heavy Chain 1 (DNAH1) encodes proteins which provide structural support for the physiological function and motor structure of spermatozoa (hereafter referred to as sperm) and ova. This study found that three single nucleotide polymorphisms (SNPs), the 27-bp insertion/deletion (InDel) mutations and three exonic copy number variations (CNVs) within DNAH1 were significantly associated with litter size of Shaanbei white cashmere goats (n = 1101). Goats with the wildtypes of these three SNPs had higher litter sizes than other carriers (p < 0.05). II genotype of the 27-bp InDel had the highest litter size compared with ID carriers (p = 0.000022). The gain genotype had the largest litter sizes compared with the loss or medium carriers for the three CNV mutations (p < 0.01). Individuals with the AA-TT-CC-II-M1-M2-M3 and AA-TT-CC-II-G1-G2-M3 combination genotypes had larger litter sizes compared with the other genotypes. This study also showed the DNAH1 expression in mothers of multiple kids was higher than mothers of single kids. These three SNPs, the 27-bp InDel and three CNVs in DNAH1 could be used as molecular markers for the selection of goat reproductive traits.